Bullying and its impact on social-emotional development in early childhood: A study in Surabaya, Indonesia - Almaziyah, Almaziyah; Fitriyah, Fifi Khoirul; Asmara, Berda; Rihlah, Jauharotur; Putri, Rachma Aliefia (Universitas Nahdlatul Ulama Surabaya, 2025)
Bullying in early childhood is a serious issue that negatively affects children’s social and emotional development. At this stage, children may act either as perpetrators or victims, both of which can influence character formation, emotional regulation, the ability to build social relationships, and the development of prosocial behavior. This study aims to examine the relationship between bullying behavior and social-emotional development in early childhood. A quantitative approach with a correlational method was employed. The sample consisted of 398 early childhood students from one early childhood education institution, selected through a total sampling technique. The research instrument used was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics, Spearman’s correlation test, cross-tabulation, and ordinal logistic regression. The findings indicate that most children fall into the low category of bullying and the moderate-to-high category of social-emotional development. Spearman’s correlation test revealed a significant positive relationship between bullying and social-emotional development (p = 0.001; r = 0.177). Furthermore, ordinal logistic regression analysis showed that social-emotional development significantly affects the level of bullying (p = 0.007; parameter estimate = 2.818). These results suggest that bullying behavior is significantly associated with the social-emotional development of early childhood students.